Cash Conversion Cycle, Asset Turnover, Capital Expenditure and Firm Value: The Mediating Role of Profitability - Iman Sofian Suriawinata; Elin Tri Budiyani; Rimi Gusliana Mais; Muhammad Anhar (Universitas Muhammadiyah Malang, 2023)
Purpose: To examine the impact of the cash conversion cycle, asset turnover, and capital expenditure on firm value, using profitability as the mediating factor. Methodology/approach: Using a sample consisting of 61 non-cyclical consumer goods listed firms in Indonesia from 2016 to 2021, a structural equation modeling is employed to analyze the direct, indirect, and total effects of the vari-ables being studied on firm value. Findings: The cash conversion cycle does not have signi-ficant direct or total effects on firm value, but it has a negative and significant indirect effect on firm value through profitability. Asset turnover and capital expen-ditures directly significantly affect firm value in different directions, but they both have positive and significant total effects on firm value. Profitability fully mediates the effect of the cash conversion cycle on firm value, and partially mediates the effect of capital expenditures on firm value. Practical implications: To ensure value creation, firms are suggested to monitor the cash conversion cycle, enhance asset turnover, and ensure the profitability of capital expenditures. Originality/value: Providing empirical evidence on the mediating role of profitability in analyzing the effect of the cash conversion cycle, asset turnover, and capital expenditures on firm value.